2003
DOI: 10.1189/jlb.1002476
|View full text |Cite
|
Sign up to set email alerts
|

The polysaccharide capsule of Cryptococcus neoformans interferes with human dendritic cell maturation and activation

Abstract: The ability of encapsulated and acapsular strains of Cryptococcus neoformans to activate dendritic cells (DC) derived from monocytes stimulated with granulocyte macrophage-colony stimulating factor and interleukin-4 was evaluated. Profound differences in DC response to encapsulated and acapsular C. neoformans strains were observed. In particular, (i) the acapsular strain was easily phagocytosed by immature DC, and the process induced several molecular markers, such as major histocompatibility complex (MHC) cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 36 publications
9
95
1
5
Order By: Relevance
“…They also showed that TNF-␣ could restore DC maturation to induce T cell responses in the presence of C. gattii, which suggested the potential of DC-based therapies to improve the outcomes of patients with C. gattii infections. Another study showed that encapsulated C. neoformans strain B3501 (serotype D) could induce human DC maturation based on DC expression of CD40, CD86, and MHC-II (28). In our study, murine BMDCs did not mature in the presence of encapsulated C. gattii strains, because they did not efficiently engulf encapsulated C. gattii strains (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…They also showed that TNF-␣ could restore DC maturation to induce T cell responses in the presence of C. gattii, which suggested the potential of DC-based therapies to improve the outcomes of patients with C. gattii infections. Another study showed that encapsulated C. neoformans strain B3501 (serotype D) could induce human DC maturation based on DC expression of CD40, CD86, and MHC-II (28). In our study, murine BMDCs did not mature in the presence of encapsulated C. gattii strains, because they did not efficiently engulf encapsulated C. gattii strains (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Macrophages and dendritic cells have been shown to bind and phagocytose acapsular, but not encapsulated, C. neoformans via macrophage mannose receptors (9,19,21,31), engagement of which, at least in some settings, has been linked to IL-6 production (35). Acapsular organisms and cryptococcal mannoprotein have been shown to induce dendritic cell maturation and activation (27,34), and mannoprotein has been shown to interact with multiple mannose receptors (24).…”
Section: Fig 7 Effect Of Depletion Of Cd25mentioning
confidence: 99%
“…GXM has profound effects on both innate and adaptive immune mechanisms. GXM can reduce MHC class II expression on APC (1, 2), inhibit activation and maturation of dendritic cells (3), reduce T cell proliferation in the presence of APC (4,5), dampen Th1 response (5,6), induce apoptosis of T cells in the presence of monocytes/macrophages via the Fas ligand/ Fas system (7), inhibit the production of proinflammatory cytokines by monocytes (8), and induce IL-10 production by monocytes (9,10).…”
Section: G Lucuronoxylomannan (Gxm)mentioning
confidence: 99%
“…The mononuclear cells were separated by density gradient centrifugation on FicollHypaque (13). Macrophages and dendritic cells were obtained as described previously (3,30).…”
Section: Preparation Of Monocytes Macrophages and Dendritic Cellsmentioning
confidence: 99%